A novel solar tracking model integrated with bistable composite structures and bimetallic strips. (15th September 2020) - Zhang, Zheng; Pei, Kai; Sun, Min; Wu, Helong; Yu, Xiaochen; Wu, Huaping; Jiang, Shaofei; Zhang, Feng
Abstract: Solar tracking model has attracted substantial academic and industrial interests owing to its high efficiency of solar panels. However, the complexity of the structure by using the mechanical structure is also increased. This paper proposes a novel solar tracking model that is composed of bistable laminates, Ni36/Mn75Ni15Cu10 bimetallic strip and organic solar cell. The bistable structure can serve as the steering mechanism and consequently reduces the number of needed parts. With the sunshine, the bimetallic strip will bend and deform due to the influence of temperature depending on the shadow area. The bending motion of Ni36/Mn75Ni15Cu10 bimetallic strip drives the bistable laminates structure snapping from one stable configuration to another, which process is reversible. The change of bistable laminates shape holds the solar cell perpendicular to light to receive the maximum solar energy. Experimental results demonstrate that the deformation process of this solar tracking model is feasible. This novel solar tracking model can be extensively used in engineering fields, due to the use of bistable laminates, the weight of the solar tracker has been greatly reduced.